Investigating the Principal Factors Influencing Bank Performance in South Africa: A Comprehensive Analysis - Rudolph, Makhathini Lungani; Aliamutu, Kansilembo (International Journal of Economics and Financial Issues, 2025)
The paper aims to explore the impact of the Capital Adequacy Ratio, Net Profit Funding, Funding to Deposit Ratio, and Operations Costs to Operational Revenue on profitability evaluated by return on assets. This research examines the banking industry, particularly the banks listed on the South Africa Stock Exchange from 2022 to 2024. This period was chosen to collect more recent data, which would enhance comprehension of the sector's present situation. The analysis indicates that the CAR value exceeds the expected significance value, suggesting that CAR does not significantly impact production. A consistently high CAR indicates that the bank is in a robust position, which often enhances performance in generating profits. The findings of this analysis demonstrate that the magnitude of the bank's capital adequacy ratio (CAR) does not significantly correlate with an increase in profit. Banking professionals are advised to prioritise the management of operational profitability and to mitigate the non-performing financing ratio (NPF) to ensure sustainable growth in bank profitability.